1992
DOI: 10.1002/hc.520030203
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3‐Selenadiazoles as precursors to cyclopentadienylcobalt dithiolenes and 1,4‐dithiins: molecular structures of bis(cycloocteno)‐1,4‐dithiin and bis(cycloocteno)‐1,4‐diselenin

Abstract: Cycloocteno

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Despite their ready preparation from 1,2,3-selenadiazoles 16 (Scheme ), little research into the chemistry of 1,4-diselenins has been documented. We have now examined the reactions of bis(cycloalkeno)-1,4-diselenins with a tributylphosphinepalladium(0) complex, and in this paper, we present the results of our study. A preliminary report of some of this work has already been published …”
Section: Introductionmentioning
confidence: 99%
“…Despite their ready preparation from 1,2,3-selenadiazoles 16 (Scheme ), little research into the chemistry of 1,4-diselenins has been documented. We have now examined the reactions of bis(cycloalkeno)-1,4-diselenins with a tributylphosphinepalladium(0) complex, and in this paper, we present the results of our study. A preliminary report of some of this work has already been published …”
Section: Introductionmentioning
confidence: 99%
“…This situation might lead to the generation of free alkyne and elemental selenium in the reaction solution, which, in the presence of elemental sulfur, might generate the dithiolene or mixed selenolatothiolato species. 168,170 Reaction of cyanide (CN − ) with elemental (neutral) sulfur to generate thiocyanate (SCN − ) has implications in biology in the context of cyanide detoxification. 171−173 Reactions of elemental sulfur and polysulfide, 174 organopolychalcogenides, 175 and transition metal−polysulfido complexes 176,177 with CN − have also been reported in the literature.…”
Section: Reactivity Of the Binuclear Co(ii)−polychalcogenido Complexe...mentioning
confidence: 99%
“…Because the selenium element has a larger atomic size in comparison with oxygen and sulfur, molecules including the selenium atom always give an increased polarizability, which, in turn, make them generally less stable than the sulfur analogues. In addition, its physical properties make selenium-containing heterocycles desirable materials in the growth of organooptic and organoelectronic materials. As a result, because 1,2,3-selenadiazoles undergo a wide variety of reactions as 1,3-dipoles and develop the synthesis of different organoselenium compounds, 1,2,3-selenadiazoles have also attracted much attention in several laboratories. , In fact, because of the reason that 1,2,3-selenadiazoles are easily separated with the loss of a nitrogen molecule and a selenium atom under both light irradiation and thermal conditions, 1,2,3-selenadiazoles have drawn attention as versatile intermediates for the preparation of alkynes. …”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, so far, there has been neither experimental nor theoretical study for the photochemical mechanisms of both 1 and 6 . It is astonishing how little is known about the mechanisms of the photochemical reactions of 1 and 6 because these molecules are so important in bioorganic and organic chemistry. Accordingly, using a more sophisticated quantum chemical theory, the study of the potential energy surfaces of 1,2,3-thiadiazole ( 1 ) and 1,2,3-thiadiazole ( 6 ) systems is undertaken. The goal of this study is to combine both observed experimental works and theoretical examinations to provide a comprehensive understanding of the excited-state behaviors of 1,2,3-thiadiazoles and 1,2,3-selenadiazoles.…”
Section: Introductionmentioning
confidence: 99%